Pricing of American Put Option under a Jump Diffusion Process with Stochastic Volatility in an Incomplete Market - Shuang Li; Yanli Zhou; Xinfeng Ruan; B. Wiwatanapataphee (Abstract and Applied Analysis)
We study the pricing of American options in an incomplete market in which the dynamics of the underlying risky asset is driven by a jump diffusion process with stochastic volatility. By employing a risk-minimization criterion, we obtain the Radon-Nikodym derivative for the minimal martingale measure and consequently a linear complementarity problem (LCP) for American option price. An iterative method is then established to solve the LCP problem for American put option price. Our numerical results show that the model and numerical scheme are robust in capturing the feature of incomplete finance market, particularly the influence of market volatility on the price of American options.